STUDI DESKRIPSI EFIKASI DIRI AKADEMIK PADA SISWA MTS AL-BADAR - Nida fauziah; Ecep Supriatna; Ardian Renata Manuardi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
This research is based on the phenomena that occur in the school. This ability must be possessed by every individual, especially students to support the success of educational goals and complete learning tasks. Students who have good academic efficacy will have a high level of success in completing their assignments. The method used in this research is descriptive quantitative. In this study using a Likert scale to measure attitudes and descriptions of students' academic self-efficacy. And the subject in the study was 105 students of Mts al-Badar Gununghalu. The results showed that the academic self-efficacy of Mts Albadar students was in the medium category 59 (56%) ), while the rest are in the low category with the number of students 22 (21%), and 24 (23%) students are in the high category. With the conclusion that students' academic self-efficacy is in a state of being reviewed from aspects that affect academic self-efficacy consisting of the level of difficulty, strength, as well as the area of activity and things that cause low academic self-efficacy and need to be improved in order to achieve goals and can complete the task optimally. Keywords: : academic self-efficacy, students,